Pengaruh Fasilitas dan Harga Terhadap Keputusan Berkunjung di Pemandian Air Panas Pariban Berastagi - Situmorang, Hilda Caroline Natalia; Sari, Dewi Comala (Civiliza Publishing, 2025)
Pariban Hot Springs is a popular tourist attraction in Berastagi that is open 24 hours and offers beautiful natural scenery surrounded by mountains. The facilities are diverse and superior, with affordable entrance ticket prices being of interest to uncover more deeply how facilities and prices play a role in the decision to visit Pariban Hot Springs Berastagi. This study aims to determine how much influence the two variables (facilities and price) have on visitor decisions. This type of research is a quantitative research method which includes validity testing, reliability testing, classical assumption testing, hypothesis testing (t test, F test, and coefficient of determination analysis test). The population of this study was 57,885 people, and the sample used was 100respondents (Slovin). Data collection was carried out through questionnairesdistributed in the form of Google forms via social media and through literature studies in the form of primary and secondary data. The results of this study indicate that both the facility and price variables have a positive and significant impact on the visiting decision variable, both partially and simultaneously. The research results from the coefficient of determination test show that the facility and price variables influence the decision to visit by 62.3% and the remaining 37.7% is influenced by other variablesnot examined in this research. Overall, facilities and prices received a high positive response, but price variables were more dominant with some items achieving total approval.